Analysis of phosphate solubilizing bacteria from mangrove sediments and their relation to the presence of waterbirds - DEVI N. CHOESIN; RESTU UTARI DEWINA (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Choesin DN, Dewina RU. 2025. Analysis of phosphate solubilizing bacteria from mangrove sediments and their relation to the presence of waterbirds. Biodiversitas 26: 2182-2188. Phosphate Solubilizing Bacteria (PSB) play a key role in the functioning of ecosystems by making insoluble phosphorus in the soil available to plants. In the mangrove ecosystem, waterbirds may also act as a phosphate source through their excretion of guano (bird droppings). The island of Pulau Rambut in Indonesia is an avian wildlife sanctuary with an uneven distribution of waterbirds in its mangrove areas. This variation in waterbird abundance is expected to affect the mangrove ecosystem and its PSB community structure. The objectives of this study were to describe the PSB community structure in mangrove sediments and relate them to the presence of waterbirds as a source of available phosphate. Five PSB species each were found in bird nesting and non-nesting sites with a Sorensen similarity of 71.4%. Molecular analysis by 16s RNA identified the predominant PSB species as Salinicola tamaricis. PSB diversity was positively correlated with soil organic carbon and negatively correlated with soil salinity, available phosphate, and total phosphate in soil (p<0.05). Total and available phosphate were higher in the bird nesting site, while PSB diversity and abundance were lower. This may be attributed to the availability of other nutrients, specifically organic carbon.